MAGIA – RELIGIA – OSTENTACJA. KAPTORGI Z WCZESNOŚREDNIOWIECZNEGO CMENTARZYSKA W RADOMIU W UJĘCIU KOMPARATYSTYCZNYM - Kurasiński, Tomasz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
This article presents an analysis of two brass lockets, rectangular in shape, discovered in a richly equipped grave no. 62 in an early-medieval grave field in Radom (the 4th quarter of the 11-12th centuries). As a result of the analysis, their cognitive value can be estimated in a comprehensive way against the background of other finds of the type excavated in graves. On the other hand, it has allowed to enrich the knowledge of burying the dead with objects of magical and religious nature. The lockets discovered in Radom were made locally, most probably as imitations of more sophisticated pendants. Most probably, they were used as containers for magical or healing amulets, possibly contact relics (brandeum, eulogiae) or perfumes. They were probably buried after mid-11th century, during the religious transformation taking place in the early Piast state, bearing material testimony to the intertwining pagan rites and the ceremonies of the new faith.